Polymorphism identification in the goat MSTN gene and association analysis with growth traits - X.P. An; J.G. Wang; J.X. Hou; H.B. Zhao; L. Bai; G. Li; L.X. Wang; X.Q. Liu; W.P. Xiao; Y.X. Song; B.Y. Cao (Czech Journal of Animal Science, 2011)
The myostatin (MSTN) gene was studied as a candidate genetic marker for growth traits. We investigated polymorphisms of the MSTN gene in 664 individuals from four goat populations and applied PCR-SSCP and DNA sequencing analysis to reveal two single nucleotide polymorphisms (DQ167575: g.368A>C (p.Lys49Thr) and g.4911C>T. At g.368A>Clocus, the frequencies of g.368A allele were 0.75-0.81, and the frequencies of g.368C allele were 0.19-0.25. At g.4911C>T locus, the frequencies of g.4911C allele were 0.76-0.82, and frequencies of g.4911T allele were 0.18-0.24. Compared to the female goats with AC genotype, those with AA genotype had superior body weight in Boer goats (15.69 ± 0.28 vs. 14.51 ± 0.31, P < 0.05) and F1 generation of Boer × Guanzhong dairy goats (19.39 ± 0.34 vs. 18.27 ± 0.33, P < 0.05). In addition, the female goats with AA genotype (45.80 ± 0.33 cm) had greater withers height than those with AC genotype (44.78 ± 0.36 cm) in F2 generation of Boer × Guanzhong dairy goats (P < 0.05). Hence, the biochemical and physiological functions along with the results obtained in our investigation suggest that the MSTN gene might play an important role in affecting the growth traits in goats.